LE-MONELAW: Lemon Peel Straw with a Combination of Pandan Extract (Pandanus amaryllifolius) as an Alternative Solution to the Plastic Straw Waste - Ahmad Habibi, Fajrin; Syadin Harjanto, Mauro; Fajar Islami, Ahmad; Muhammad Izzan Faza, Aufa; Sauqi Zhahir, Ahmadan (SMA Trensains Muhammadiyah Sragen, 2023)
Plastic waste is a serious problem that must be addressed immediately. Plastic waste reaches 17.7% of national waste according to data from the national waste management information system (SIPSN). In fact, Indonesia is currently a producer of 93 million units of plastic straw waste per day. The purpose of this study was to determine the effectiveness of making straws from lemon peel waste combined with pandan extract as an alternative solution to the plastic straw waste. This type of research is descriptive with a quantitative approach. The description focuses on product manufacturing and product testing. Data collection by observation and literature study. Observations were made to determine the effectiveness of the product and a literature study was conducted to analyze the content of pandan leaves. Product effectiveness indicator if all tests are fulfilled. The data analysis technique used is descriptive quantitative. The results of the effectiveness test showed that the straw smelled of pandan and was tasteless, the endurance test was 14.2 minutes, and the product expiration test lasted up to 22 days. From the test results concluded that the product is effective. The research suggests is that future researchers can use suitable straw molds to get a good shape.